Efeito de protocolo para a mudança do estilo de vida (MEV) sobre a glicemia de jejum em adultos - Torezan, Gabriel Augusto [UNESP] (2014)
Introduction: Type 2 Diabetes Mellitus is an emerging public health problem in Brazil and worldwide and is associated with behavioral components including dietary intake, physical inactivity and obesity. The lifestyle change programs through the practice of physical exercises and dietary advice proves to be the most effective therapy for the treatment and prevention of T2DM and glucose amendment. Objective: Verify the efficacy of 20 weeks lifestyle change program on fasting glucose. Methods: We evaluated 237 free living people participating in the lifestyle change program (diet and physical activity) Mexa-se Pró-Saúde, in which 121 of the participants completed the 20 week intervention. Patients were evaluated for biochemical profiles, anthropometric and nutritional assessment, physical fitness assessment. Results: 27.28% of the participants some degree of glycemic change were reclassificated with 15,15% being normalized. The dietary component variety was related to a risk of 8 % ( CI estimate of 0.0768 ( 0.0009 to 0.1527 ) in the increase in blood glucose and presenting an odds ratio of IC 1.079826 ( 1.0009 to 1.164975 ) to glycemic alterations . Conclusion : The poor quality of the low diet mainly by low intake of food groups that are considered protective influence food variety as a risk component in this population mainly by low qualitative and quantitative intake of cereals , fruits, vegetables and fiber